How caregiving nutrition/dietetics majors experience home foodwork - Hoss-Cruz, Kathleen M (My University, 2024)
The purpose of the research was to explore how female nutrition/dietetics majors at a large, Midwestern university, with a caregiving role in their home, interpreted their roles in home foodwork, how their formally acquired nutrition knowledge influenced that role, and how they saw their role in home foodwork shaping their careers. These future nutrition professionals will enter a field that focuses on individual behavior change to address the systemic issues of nutrient-poor dietary patterns and rising rates of non-communicable disease and other chronic health conditions. Using social reproduction theory as my conceptual framework, I conducted an Interpretive Phenomenological Analysis of a total of eighteen interviews conducted with six participants who met the participant criteria. I analyzed each interview through a multi-step coding and theming process which ended by comparing themes across all six participants. All participants had primary responsibility for foodwork in their homes with varying levels of assistance from family members. They faced challenges in meeting foodwork goals including time poverty, family food preferences, and gendered expectations. Participants prioritized nutrient-dense foods in their homes, but this required trade-offs in other areas of social reproduction. Based on this finding and the evidence from the literature review, I concluded that social reproduction in the home is not something one adult—or even a nuclear family—can do well alone. To facilitate the foodwork aspect of social reproduction, families need access to nutrient-dense, affordable convenience foods; a safe place in which to experiment with new foods and recipes without spending their own money; initiation and/or restoration of government programs that support foodwork and other social reproduction activities; and a dietetics profession that is more critical of the structural inequities that lead to nutrient-poor dietary patterns in the first place.
Keywords: Interpretive phenomenological analysis; Social reproduction theory; Neoliberalism; Critical dietetics; Foodwork; Post-traditional students